BOBOT, BIBIT, BEBET: ANALISIS STRATEGI PEMENANGAN PRABOWO-GIBRAN PADA PILPRES 2024 MELALUI POLITIK KETOKOHAN - Erwin Kartinawati; Andrik Purwasito; Betty Gama (Universitas Tidar, 2026)
Long before the 2024 presidential election campaign period was set, billboards with pictures of Prabowo-Jokowi had embellished several cities and regions in Indonesia. That was interesting because in his fifth candidacy for president of the Republic of Indonesia, Prabowo did not take Jokowi but Jokowi's son, Gibran Rakabuming Raka. Why did the billboards as a medium for political outreach not directly display the picture of Prabowo-Gibran, but instead Prabowo-Jokowi? Through a semiotic analysis of the Charles Sanders Pierce model which connects three elements between sign, object and interpretant, it was concluded that this was part of an effort to win a candidate partner using a political figure srategy. Jokowi is the political branding for Gibran. Branding is needed to increase electability through popularity. Jokowi's figure on the billboards was a political strategy through a primarily Javanese cultural approach that could not ignore the issues of Bibit, Bobot, and Bebet. All three were forms of political negotiation by demonstrating the power possessed to gain a bargaining position against opponents and the public, through cultural awareness.